CORRELATION OF RELIGIOUS LITERACY AND CULTURAL LITERACY TOWARDS RELIGIOUS MODERATION - Nur Fikriya, Kinanthi; Widyaningrum, Retno (BRIGHT VISION Journal of Language and Education, 2024)
This quantitative research aims to investigate the influence of religious literacy and cultural literacy on religious moderation in students of the Postgraduate Islamic Religious Education (PAI) B Study Program at the State Islamic Institute (IAIN) Ponorogo. This research uses a quantitative approach with a correlational study design. Data was collected through a questionnaire that measured the level of religious literacy, cultural literacy and religious moderation. Data analysis was carried out using multiple linear regression techniques. The results of the research show that there is a positive and significant influence of religious literacy and cultural literacy on religious moderation in PAI B Postgraduate students at IAIN Ponorogo. This means that students who have a high level of religious literacy and cultural literacy tend to have a better level of religious moderation. These findings show the importance of developing religious literacy and cultural literacy in increasing attitudes of tolerance and better understanding of religious and cultural differences among PAI students.